Peran Kontraktor dalam Peningkatan Constructability pada Pembangunan Jalan Jembatan Wilayah Kalimantan Timur - Sulistio, Hendrik; Magawaty, Magawaty (Department of Civil Engineering, Diponegoro University, 2013)
Contructability has been defined as the optimus usefull of construction knowledgeand experience in planning design, procurement and field operation to achieve overall can be effective, efficiency efficiency and good quality (CII, Uaustin, USA). Successful application from constructability improvement suspended commited from overall group Project Management Team for achievent of project goals. Project Management Team is referred between the project owner, architect or designer and the construction company before construction commences. Purpuse of observing is understanding set construction company manager in practice concept constructability in goal construction project for achieve improvement of performance and optimum project can be efficiency can be saved. Object observe focust in build of road and bridge in East Borneo with sample are construction company manager with questionare after that with Analysis Static Parametric. Result of Improtance Analysis is 6.32 and result of performance analysis is enough high but has separated from importance in project management road is 10.42%. Result of factor analysis can see that responden toward conceptual constructability can more complication with capability controlling time schedule. One manner can be use for controlling time implementation is do “Construction Method” as well, can do improving quality and safety implementation.